Gut Microbiota (IntechOpen, 2023)
The gut-brain axis has gained considerable attention from different branches of the scientific community in recent years. In this book, scientists from different disciplines present current scientific knowledge on the topic. The interaction between the prokaryote and eukaryote cells stimulates the evolutionary processes, and results in various systemic illnesses such as neuropsychiatric disorders and may help the continuity of health. Nature has provided us with healthy food that builds our pharmacy. This natural pharmacy store may help the body's healing processes through its effects on gut microbiota and the immune system. This book aims to provide the reader with detailed analyses of the current scientific knowledge on the gut-brain axis and its relation with health and disease. We hope that the reader benefits from the presented material.